2015
DOI: 10.13065/jksdh.2015.15.06.947
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and oral diseases in the middle aged and elderly people

Abstract: Objectives:The purpose of the study was to identify the relationship between metabolic syndrome and oral diseases in the middle aged and elderly in Korea. Methods:The study subjects were 6,390 people over 40 years old from 2010 and 2012 Korea National Health and Nutrition Examination Survey. The survey questionnaire consisted of health, nutrition, and oral examination surveys. The independent variables included general characteristics, health behavior, oral health behavior, and metabolic syndrome. The dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Song and Lee [29] also reported that the number of remaining teeth was low in patients with chronic diseases, such as diabetes and hyperlipidemia. This was similar to the findings of a study by Oh [20], which showed a high prevalence of tooth loss in the hypertension, obesity, and disease morbidity groups, as well as a study by Kang et al [30], which showed a 1.25-and 1.47-times higher loss of teeth in the hypertension and MetS groups, respectively, than in the non-disease group. In a study by Lee et al [16], dyslipidemia and hypertriglyceridemia were significantly correlated with the number of remaining teeth, and the number of remaining teeth was low in people with MetS, similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Song and Lee [29] also reported that the number of remaining teeth was low in patients with chronic diseases, such as diabetes and hyperlipidemia. This was similar to the findings of a study by Oh [20], which showed a high prevalence of tooth loss in the hypertension, obesity, and disease morbidity groups, as well as a study by Kang et al [30], which showed a 1.25-and 1.47-times higher loss of teeth in the hypertension and MetS groups, respectively, than in the non-disease group. In a study by Lee et al [16], dyslipidemia and hypertriglyceridemia were significantly correlated with the number of remaining teeth, and the number of remaining teeth was low in people with MetS, similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Several determinants, such as the age, education level, and demographic socioeconomic status, are associated with oral health-related behaviors, such as dental caries, periodontal conditions, and smoking in postmenopausal women, and tooth loss can be a complex measure of dental disease [31]. In addition, various chronic diseases are believed to cause inflammation in the teeth and periodontium and appear as a result of tooth loss [30]. In addition, postmenopausal hormone replacement therapy has a positive effect on maintaining natural teeth; therefore, the lack of hormone replacement therapy can be considered as an independent risk indicator for tooth loss in postmenopausal women [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lower the educational level, the higher was the chewing difficulty. This is in line with research by Kang and Yu 28) who studied metabolic syndrome and oral disease, and found that the lower the educational level, the higher the periodontitis and the lower the educational level, the higher the missing value. In addition, the study by Hawg et al 29) proved that the lower the education level, the more chewing difficulty was, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, it was significant in diabetes and abdominal obesity, and it was consistent with the study results of Han [42], which showed a significant association with CPI as the number of risk factors for MetS increased. According to Kang et al [43], the prevalence of periodontitis was significantly higher in fasting glucose, HDL cholesterol, and abdominal obesity, and the odds ratio for hypertension was significantly higher in the model corrected for health behavior and oral health behavior. According to a Kim [37], the risk of periodontitis in the hypertensive group was 1.60 times higher whereas the risk of periodontal disease was 2.22 times higher when 1 or more MetS risk factors were present.…”
Section: Discussionmentioning
confidence: 98%